Ablation of cerebellar nuclei prevents H-reflex down-conditioning in rats - Chen, Xiang Yang (Cold Spring Harbor Laboratory Press, 2005)
While studies of cerebellar involvement in learning and memory have described plasticity within the cerebellum, its role in acquisition of plasticity elsewhere in the CNS is largely unexplored. This study set out to determine whether the cerebellum is needed for acquisition of the spinal cord plasticity that underlies operantly conditioned decrease in the H-reflex, the electrical analog of the spinal stretch reflex. Rats in which the cerebellar output nuclei dentate and interpositus (DIN) had been ablated were exposed for 50 d to the H-reflex down-conditioning protocol. DIN ablation, which in itself had no significant long-term effect on H-reflex size, entirely prevented acquisition of a smaller H-reflex. Since previous studies show that corticospinal tract (CST) transection also prevents down-conditioning while transection of the rubrospinal tract and other major descending tracts does not, this result implies that DIN output that affects cortex is essential for generation of the CST activity that induces the spinal cord plasticity, which is, in turn, directly responsible for the smaller H-reflex. The result extends the role of the cerebellum in learning and memory to include participation in induction of plasticity elsewhere in the CNS, specifically in the spinal cord. The cerebellum might simply support processes in sensorimotor cortex or elsewhere that change the spinal cord, or the cerebellum itself might undergo plasticity similar to that occurring with vestibulo-ocular reflex (VOR) or eyeblink conditioning.